Ability to use the wait-and-see strategy in pathological gamblers. Issue 2 (15th December 2015) - Kertzman, Semion; Vainder, Michael; Visne, Tali; Aizer, Anat; Kotler, Moshe; Dannon, Pinhas N.
Abstract: Pathological gamblers (PGs) perform differently on neurocognitive tests than do healthy controls (HC). The aim of this study was to assess "waiting ability" – a major components of inhibition control-using a modified Stop Signal Task (SST) in a population of male PGs ( N =55), and HCs ( N =53). Results indicated no differences between PGs and HCs in reaction times, intra-individual response variability, or number of false alarms and misses. In conclusion, PGs were not impaired in their ability to manipulate their on-line response strategy during the experimental task and were instead able to change their strategy to decrease the number of false alarms. However, much more empirical and theoretical work needs to be carried out in order to understand the key neural basis of impulsivity among PGs. Highlights: We hypothesized that PGs with an impaired waiting ability should have a higher number of false alarms during performance that required an ability to ignore a Go stimulus in face of the next Stop stimulus. Pathological gamblers who use an exaggerated waiting strategy should have a higher number of misses during performance. Our study provides evidence for the role of a waiting strategy as a moderator of increasing cognitive control. Waiting ability is seen as a specific cognitive capacity that includes a number of factors ranging from low-level sensory to high-level cognitive processes. Our results suggest that PGs and HCs were successful in their ability to adapt their responses and prevent unwanted responses.